DEVELOPMENT OF METHODOLOGICAL CULTURE OF FUTURE LECTURERS OF HIGHER EDUCATION INSTITUTIONS AT THE STAGE OF PROFESSIONAL TRAINING - Salyha, Nataliia (Mountain School of Ukrainian Carpaty, 2020)
The article deals with the problem of developing the methodological culture of future lecturers of higher education institutions (HEI) at the stage of professional training. It is focused on the need to prepare future lecturers to working with student youth. The article presents the characteristics of the methodological culture of a lecturer of higher education institution, substantiates the necessity of its development for successful professional activity in conditions of reforms in higher education, analyzes the features and functionality of the pedagogical environment, its role in the system of professional training of future lecturers. It analyzes scientific approaches to the definition of the concept of «methodological culture» and specifies the nature of the phenomenon called «methodological culture of the future HEI lecturer». It offers the ways to develop the methodological culture of the future lecturer at the stage of obtaining the master’s degree as well. The relevance of the article is evident in the substantiation of the content and components of the methodological culture of the future HEI lecturer; in the training of a lecturer who has mastered new technologies, methods, forms, means of teaching and educating student youth; in identifying potential opportunities within the educational space of an higher education institution. Abiding by pedagogical conditions (filling the content of disciplines with knowledge about methodological culture of the HEI lecturer; use of interactive technologies in order to increase the motivation of students to develop their own methodological culture; taking into account age-related peculiarities of student youth) provides constant purposeful influence on development of the researched quality. The author proves the importance of developing the methodological culture of the lecturer as one of the important personal and professional qualities and notes that this is a complex, multilevel and systematic formation. The article emphasizes that the content of the subjects of the psychological and pedagogical cycle taught in the specialty «Educational, Pedagogical Sciences» promotes the growth of professionalism, enrichment of knowledge as well as ensures the development of a holistic creative personality and forms the methodological culture of future lecturers. Despite the large number of scientific papers dealing with the study of various aspects of the methodological culture of the future lecturers of higher education institution, it should be noted that there is no well-established definition of this concept in the psychological and pedagogical literature yet. Research methods were aimed at describing the essence of the article content, a presenting the holistic view of the problem mentioned in the title. The results of scientific research showed that there is an urgent need to improve scientific idea about the essence and structure of the concept of «methodological culture of the future HEI lecturer», to identify its structural components, principles and factors of its formation. Research of the methodological culture of the future lecturers with an aim to improve the efficiency of further professional activity and development of their professional and personal qualities deserves further consideration.